Taeniasis saginata infection prevalence in raw beef lawar consumers, in Sukawati Sub-District, Gianyar, 2012 - Oka Harimbawa; Anak Agung Sagung Sawitri; I Nyoman Adiputra (Universitas Udayana, 2013)
Research indicates that taeniasis and cysticocircosis are endemic in Bali with increasing trend found each year. Previous research in Gianyar District indicated that taeniasis prevalence was 23.8%, with the highest prevalence found in the sub-district of Sukawati. This high prevalence is partly influenced by the community practices and a culture of raw beef consumption in this area. This research used a combination of quantitative and qualitative methods. Quantitative data was collected through cross sectional analysis of 80 samples of raw beef consumers (interviews on risk behaviours and past experience). Fecal samples from these respondents were also taken and examined for taeniasis saginata infection. Qualitative data was collected through participatory observation and in-depth interviews with raw beef foodstall owners. The research findings indicated that the percentage of taeniasis saginata infection was found predominantly in the 15-44 age group, were male and did not have a formal education. Bivariate analysis indicated that the most significant factors were gender (p=0.018), location of foodstall (p=0.001) and respondent lawar consumption frequency (p=0.013). Multivariate analysis using cox regression methods found that the location of foodstall had a significant correlation with the occurrence of taeniasis saginata (p=0.003). Recommendations include education for raw beef providers and upscaled testing of consumers and further research into other variables such as livestock slaughter behaviours and meat preparation protocols.